Voices in the park: Researching the participation of young children in outdoor play in early years settings. (October 2014) - Waller, Tim
This article critically reflects on the participation of young children aged 3–4 years in an ongoing outdoor learning project started in 2004. The aims of the research are to investigate children's dispositions within the outdoor environment, to elicit children's perspectives of their outdoor experiences and to investigate the relationship between outdoor environments and pedagogy in early childhood. The article analyses the research findings from a sociocultural perspective focusing on transformations of participation. This project has adapted the multi-method 'Mosaic approach' described by Clark and Moss. In particular, a variety of 'participatory tools' with children are used to document and reflect on learning. The article critically discusses findings from the project and identifies a number of significant implications for participatory research with young children, early childhood pedagogy and management in early childhood settings.